Crystal Structure of Lu2.92Ce0.08MgAl3SiO12 Garnet Phosphor and Its Photoluminescent Properties. Issue 2 (11th September 2015) - Cho, Kyoungwon; Choi, Jaeha; Mhin, Sungwook; Kim, Kang Min; Lee, Jung‐Il; Ryu, Jeong Ho
Abstract : A novel Ce 3+ ‐doped Lu3 MgAl3 SiO12 (LCMAS) phosphor was successfully synthesized by a conventional solid‐state reaction. The crystal structure of the LCMAS was characterized by Rietveld refinement. The broad emission spectra of the LCMAS were observed at 550 nm, and the temperature dependence on photoluminescence properties of the LCMAS was investigated. Also, the activation energy for thermal quenching was determined by Arrhenius fitting. The experimental results clearly indicate that the LCMAS phosphor has a great potential for the down‐conversion of yellow phosphor into white light‐emitting diodes.